Effect of Bulge Geometry on Impact Behaviour of Front Platform of Compressed Natural Gas Vehicle - Abdul Rahim, Norwazan (2007)
The effects of structural geometry and reinforcement part on the crash behaviour have been investigated throughout this study. The crash analysis under lateral (side) impact has been investigated on crash behaviour in term of crash distance and energy absorption on front platform also the deformation shape of model. The crash behaviour studies for the geometry were analyzed in two different conditions which is the different bulge height and length attached on the front platform. In this case, the front platform was modified from the base front platform (without bulge) and joined the bulge plate together on the top of platform. This all the platform has been studies to compare their characteristic independently.The next section of analyses, the front platform are attached with all other parts was studied between different pattern and thickness of the side member and center member assembly front floor. The mounting parts for the CNG tank underneath front platform consisted of the mounting bracket, mounting strap and bottom reinforcement are also attached to this assembly. All the parts are known as a reinforcement parts. Firstly, the entire model are being studies on different pattern and continuing with the different thickness of the side member and center member assembly front floor. In the analytical work, finite element analyses were generated by using the HYPERMESH software and it has been analyzed using the LS DYNA software. In early stage, before the finite element models were created, the design stage of model is using the CATIA V5, 3D design software. From the results obtained, the final stage of analyses have been achieved that the front platform with the new the side member and center member assembly front floor is the best front platform to use as the fabrication work. The exactly thickness of the side member and center member assembly front floor is 1.2 mm.